A changing democracy: contemporary challenges to the British political tradition. (4th July 2018) - Hall, Matthew; Marsh, David; Vines, Emma
ABSTRACT: A series of authors including ourselves have argued that there is a dominant, if contested, political tradition (the BPT), that is a particular conception of democracy, that underpins to institutions and processes of British politics. However, here we argue that the BPT has never been more contested or vulnerable, focusing upon three contemporary challenges, the Scottish question, the rise of anti-politics and the demands to leave the European Union (EU), culminating in BREXIT, although we recognise there are others. At the same time, we contend that the BPT still plays a key role in how the political elite reacts to these challenges; its first response remains to preserve as much of the BPT as possible in changing circumstances. As such, the key question we address here is whether we are witnessing the beginnings of a fundamental shift in the nature of British political democracy, or whether, as so often before, the BPT and its adherents will adapt to, and accommodate, these challenges.